Self Care for Overcoming Sleep Disorders in Cancer Patients: Literature Review - Nurfitriani, Putri; Gayatri, Dewi (Jurnal Berita Ilmu Keperawatan, 2024)
Cancer can cause pain, weakness, sleep problems, and fatigue, and affect functional limitations that affect daily life. One of the most common and frequently complained symptoms in cancer patients is sleep disturbance. This paper aims to determine the effect of self-care to overcome sleep disorders in cancer patients. The author uses several databases, such as Scopus, SpringerLink, and Sage Journal. Clinical Key Nursing for use in the search for relevant articles. There are a total of 8 articles have been analyzed where several self-care interventions are used to treat sleep disorders in cancer patients, including mindfulness, exercise, yoga, dance, and personal psychotherapy. most of them showed results in a decrease in sleep disturbances in cancer patients, but there was one article that did not show significant results related to sleep disturbances. All the articles found were forms of intervention from self-care. There are three articles related to insomnia, one related to sleep quality, and four others related to sleep disturbance. Based on several journals that have been analyzed, it can be concluded that the provision of self-care interventions can affect the incidence of sleep disorders in cancer patients. A practical and secure method, exemplified by self-care practices, seeks to enhance sleep quality, general comfort, and the patient’s overall quality of life.